Demystifying and Mitigating Code-Dependent Switching Distortions in Current-Steering DACs - Lai, Longqiang; Li, Xueqing; Fu, Yushen; Liu, Yongpan; Yang, Huazhong (IEEE transactions on circuits and systems. I, Regular papers, 2019)
This paper analyzes the intermodulation between the element transition rate and the output-dependent unit switching distortion, i.e., the switching distortion of one switching unit, in current-steering digital-to-analog converters (DACs). The analysis and experimental results reveal how this intermodulation affects the DAC linearity. Based on this, we also propose a technique, termed random pairwise swapping (RPS) to improve the linearity of dynamic-element-matching-decoded DACs. Compared with existing techniques, RPS needs no half-cycle RZ operations and, thus, has no related vulnerabilities. In addition, the RPS could deal with the mismatch between different channels effectively. A 14-bit experimental DAC is fabricated in a 65-nm CMOS process. Measured results at 1.0-GS/s show above 72-dBc SFDR within 422-MHz band-width and 8-10-dB image tone suppression by the proposed RPS technique. At 3.0 GS/s, the SFDR is over 60 dBc within 600-MHz bandwidth.